O papel lógico-epistemológico da autoconsciência na filosofia sânscrita clássica - Lima, Danillo Costa (2024)
This investigation focuses on the problematic of the nature of self-knowledge and the epistemic interdependence between self-knowledge and world-knowledge, for which two primary approaches are possible: either prioritizing being to explain knowledge (as exemplified by Nyāya-Vaiśeṣika) or prioritizing knowledge to explain being (as seen in Yogācāra, Sāṁkhya and Vedānta). On the former, the philosopher proceeds by devising the means for knowing being and the categories in which being may be thought, so as to subsequently proceed to apply these means and categories to understand himself; if the latter, the philosopher begins by clarifying his own self-awareness so as to then derive from it the means by which he can know and the categories within which what he knows must fall. It is found that these two approaches rely on two distinct models of selfconsciousness: an intentional or higher-order theory (anuvyavasāya) and a pre-reflexive self-awareness (svasaṁvedana). The Pratyabhijñā school, or the “School of Recognition”", comes at the crust of this debate and offers a unique form of synthesis of these approaches in that, while belonging to the latter camp, it seeks to transcendentally recover and justify the philosophical project of the former, giving rise to a philosophy that is epistemically constructivist and phenomenological, with a model of transcendental and dialectical logic that is pragmatist and pan-semiotic